Strategy for Optimizing Oil Palm Plantation Productivity Through Barangan Banana Intercropping During Replanting Period (Case Study: PT Agricinal) - Daniel Martahi Bonar Manurung; Hermanto Siregar; Hendro Sasongko (Pelopor Publikasi Akademika, 2026)
The declining productivity of oil palm plantations exceeding the optimal productive age (>25 years) poses significant financial challenges for plantation companies. PT Agricinal experienced a drastic decrease in Fresh Fruit Bunch (FFB) productivity from 6.41 tons/ha/year in 2020 to 3.92 tons/ha/year in 2022—far below the ideal standard of 25–30 tons/ha/year. This condition triggered a replanting decision in 2022 but created a 3–4-year non-productive period (Tanaman Belum Menghasilkan/TBM) without operational revenue. This research aims to analyze the financial feasibility of Barangan banana intercropping on 1,000 ha of replanting land as a revenue optimization solution. The research methodology employs a mixed-methods approach that combines quantitative business feasibility analysis—using Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (Net B/C), Payback Period (PP), sensitivity analysis, and SWOT analysis indicators—with qualitative insights. Research findings demonstrate that Barangan banana intercropping provides significant improvements in financial feasibility: NPV increased 66.8%, from IDR 58.63 billion to IDR 97.79 billion; IRR increased from 25% to 45%; Net B/C increased from 1.65 to 1.77; and Payback Period shortened from 6 years to 4 years. Sensitivity analysis proves the project's resilience to fluctuations in CPO prices, operational costs, and FFB productivity. The intercropping strategy effectively fills cash flow gaps during the TBM period, enhances land use efficiency, and strengthens plantation business competitiveness. This research concludes that implementing Barangan banana intercropping on oil palm replanting land is feasible and strategic for large-scale application as a sustainable agribusiness model.